Development of in-situ Al-A12Cu functionally graded materials by a centrifugal method. (29th October 2004) - Oike, Shin; Watanabe, Yoshimi
In this study, in-situ Al-A12 Cu FGMs were fabricated by a centrifugal method using hypo-eutectic, eutectic and hyper-eutectic Al-Cu alloys. The microstructures and mechanical properties of in-situ Al-A12 Cu FGMs were studied. It was found that the in-situ FGMs could be fabricated by using not only hypo-eutectic or hyper-eutectic alloys but also a eutectic alloy. The particle sizes of the A12 Cu and Al primary crystals were dependent upon their location in the ring thickness. It was also found that a notable position dependence on the mechanical properties exists. It was concluded that the partial separation of Al and Cu atoms in the liquid state occurred during the early stage of centrifugal processing, prior to the migration of primary crystals.